2011
DOI: 10.1115/1.4005040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cross Section Reduction on the Mechanical Properties of Aluminium Tubes Drawn With Variable Wall Thickness

Abstract: Effect of cross section reduction on the mechanical properties of aluminium tubes drawn with variable wall thickness

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Usually, magnesium (Mg) alloy microtubes are currently the most popular metallic materials for stents, which are typically made by laser-cutting a thin-walled microtube [6]. Die drawing such as hollow sinking has been used for fabricating microtubes [7][8][9][10]. However, tubes made of materials with low plasticity, such as Mg and Ni-Ti alloys, often break under a large reduction in the cross-sectional area during cold die drawing [5,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, magnesium (Mg) alloy microtubes are currently the most popular metallic materials for stents, which are typically made by laser-cutting a thin-walled microtube [6]. Die drawing such as hollow sinking has been used for fabricating microtubes [7][8][9][10]. However, tubes made of materials with low plasticity, such as Mg and Ni-Ti alloys, often break under a large reduction in the cross-sectional area during cold die drawing [5,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed regarding drawing speed that velocities of 2 and 5 m/min would be more suitable for under pressure lubrication as well as reduction in tensile force [8]. Bui et al (2011) explored effect of level of reduction at cross-section of aluminate tube on the given mechanical properties in cold-drawing process. They showed that rising deformation has increased micro hardness, yield strength and ultimate tensile strength in samples; on the one hand, and reduced correspondent strain to ultimate tensile strength point and elongation, on the other hand [12].…”
Section: Introduction *mentioning
confidence: 99%
“…Bui et al (2011) explored effect of level of reduction at cross-section of aluminate tube on the given mechanical properties in cold-drawing process. They showed that rising deformation has increased micro hardness, yield strength and ultimate tensile strength in samples; on the one hand, and reduced correspondent strain to ultimate tensile strength point and elongation, on the other hand [12]. Gattmah et al (2017) have examined residual stress in cold-drawing process in steel tube (AISI 1010).…”
Section: Introduction *mentioning
confidence: 99%
“…On the other hand, the welds made with a conical tool pin profile have the lowest tensile strength and elongation, suggesting that this tool profile results in weaker and less ductile welds. Bui et al (2011) performed experiments to investigate how reducing the cross-sectional area of variable thickness of aluminium tubes affects their microstructure and mechanical properties. Two distinct position-controlled mandrel techniques were employed to draw the tubes, and their mechanical properties were assessed in relation to the cross-sectional reduction.…”
mentioning
confidence: 99%